Ermenegildo Florit e la Dei Verbum - Tarocchi Tarocchi, Stefano (Poznańskie Studia Teologiczne, 2014)
The article by Stefano Tarocchi titled Ermenegildo Florit and “Dei Verbum” presents the contribution of the then Archbishop of Florence and his accompanying theologian Rev. Umberto Betti in the writing of the constitution on the Revelation of the Second Vatican Council. Based on the Diario del Concilio of the Florentine theologian and his correspondence with the Archbishop the author shows in a chronological order not only the participation of the Archbishop in the work of the theological commission that prepared subsequent versions of the document, but also scrupulously recounts the particular propositions modifying the versions of the document, expounding in this way the contribution of the two Florentines to the emergence of the constitution Dei Verbum against the background of subsequent stages of the shaping of this conciliar document.